When prison gangs become organized crime: Studying protection arrangements and their consequences - Gundur, Rajeev Vishwanath (Trends in organized crime, 2022)
Despite interest in the subject, the study of prison gangs has been meagre since the late 1980s. Occasional studies appear, but they tend to focus on only the largest prison systems in the US. This introduction to this special issue, Prison Gangs as Organized Crime, provides an overview of notable literature on the emergence and evolution of prison gangs, their relationships with protection, and their organized criminal activities. Moreover, the articles in this special issue explore important questions: How might we study prison gangs at a large scale? How do prison administrators’ responses to prison gangs cause prison gangs to adjust their power structures? How do prison gangs seek to establish protection arrangements? And what happens when prison gangs successfully establish protection arrangements beyond prison walls?